The nexus of streamers’ factors on shopping happiness toward impulse purchases in live streaming e-commerce - Kurnia Kurnia; Ferdi Antonio (International Journal of Economics Development Research (IJEDR), 2023)
A new trend in live-streaming shopping indicates a unique relationship between streamers and viewers. Streamers in the live streaming platform appeal to consumers’ perceptions and purchase behavior by stimulating consumers’ emotions. Consequently, positive emotions, such as enjoyment and happiness can trigger impulse buying. This research developed a research model based on the Theory of Interpersonal Behavior (TIB) to examine the influence of streamers on shopping happiness and then its impact on impulse purchases in the fashion apparel product category which is marketed via TikTok e-commerce live-streaming in Indonesia. Consumers who have purchased in live streaming TikTok were the respondents of this study. Purposive sampling was deployed with a questionnaire using a Likert scale. There were 405 eligible respondents analyzed by Structural Equation Modeling (PLS-SEM). The result showed that the model proposed in this research has strong predictive validity in predicting impulse purchases. The findings demonstrated that shopping happiness has a positive impact on impulse purchases on live-streaming platforms. In addition, the results indicate that factors inherent in streamers, namely streamer popularity, streamer reputation, and streamer product, have a significant influence (p-value < 0.05, CI 95%) on viewers' positive emotions. The Streamer factors that strongest influence shopping happiness were found in streamer popularity, followed by streamer reputation, while the weakest was from streamer product fit. Furthermore, it was revealed that sensation-seeking strengthens the influence of popular streamers and product fit to shopping happiness.